2006
DOI: 10.1590/s0101-31222006000200019
|View full text |Cite
|
Sign up to set email alerts
|

Influência do repouso pós-colheita de frutos na qualidade fisiológica de sementes de mamão

Abstract: Para avaliar a influência do repouso pós-colheita de frutos de mamão, sobre as alterações na qualidade fisiológica das sementes, este trabalho foi conduzido no Laboratório de Fitotecnia no Setor de Produção e Tecnologia de Sementes da Universidade Estadual do Norte Fluminense Darcy Ribeiro, em Campos dos Goytacazes-RJ. As sementes dos genótipos Solo e Formosa provenientes de frutos hermafroditas, foram colhidos no estádio de maturação II (1/4 fruto maduro). A extração das sementes foi realizada logo após a col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 1 publication
2
8
0
7
Order By: Relevance
“…The results found in this work are consistent with the requirements of the fruit market of the "Solo" group, which is of the order of 11.5 °Brix (Fagundes & Yamanishi, 2001). Martins et al (2006) and Grizotto, Berbari, Moura and Claus (2006), observed that SS values should be 11.5 to 11.6 °Brix in the fruit pulp, being this dependent on the maturation stage at which the fruit is harvested (M. I. F. Chitarra & A. B. Chitarra, 2005).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The results found in this work are consistent with the requirements of the fruit market of the "Solo" group, which is of the order of 11.5 °Brix (Fagundes & Yamanishi, 2001). Martins et al (2006) and Grizotto, Berbari, Moura and Claus (2006), observed that SS values should be 11.5 to 11.6 °Brix in the fruit pulp, being this dependent on the maturation stage at which the fruit is harvested (M. I. F. Chitarra & A. B. Chitarra, 2005).…”
Section: Resultssupporting
confidence: 89%
“…The GFT and the MFT of the pulp ranged from 2.76 to 3.65 and 2.04 to 2.65 cm among the evaluated hybrids, presenting average values close to 2.00 cm, considered ideal value for commercialization (Martins et al, 2006). Oliveira et al (2010) observed a significant and positive correlation, although of low magnitude (0.42), between pulp thickness and fruit firmness.…”
Section: Resultsmentioning
confidence: 90%
“…A manutenção das sementes no fruto após a colheita contribui para a melhoria da qualidade das sementes, o que estaria associado a alguma alteração entre promotores e inibidores de germinação no interior das sementes (MARTINS et al, 2006 Tabela 1 -Porcentagem de germinação, primeira contagem, sementes dormentes pelo teste de tetrazólio e germinação após o envelhecimento acelerado em sementes de mamão com e sem sarcotesta, extraídas de frutos em quatro estádios de maturação nas duas épocas de colheita.…”
Section: Resultsunclassified
“…GTP and STP ranged from 2.56 to 4.02 and 1.74 to 2.86 cm, respectively, between the evaluated cultivars, with means close to 2.0 cm (Table 2), which is the thickness considered ideal for commercialization (Martins et al, 2006). Oliveira et al (2010) observed a significant and positive correlation, although low (0.42), between pulp thickness and fruit firmness.…”
Section: Resultsmentioning
confidence: 92%
“…The plants, previously labeled, and their flowers were individually protected with waterproof paper bags to prevent contamination with undesirable pollen and crosses were identified with plastic labels. Fruits were harvested at 135 to 150 days after pollination at maturation stage 1 (1/4 of the fruit was yellow) and stored for 7 to 10 days at room temperature, according to Martins et al (2006) and Aroucha et al (2005), with enough time to allow seeds to reach the point of total physiological maturity and maximum germination and vigor.…”
Section: Methodsmentioning
confidence: 99%